Influence of Gender on Smile Characteristics; Gingival Display and Exposure of Maxillary Central Incisor - Khan, Mehwish; Musharraf, Hira; Yousuf, Waqas; Ahmed, Jamshed (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To evaluate the relationship of gingival display and amount of maxillary central incisor exposure with genders dimorphism during posed smiles. Methodology: A cross-sectional study was conducted from May to November 2018 in the Department of Prosthodontics in a private dental teaching hospital, Karachi. Total 154 subjects were selected using a consecutive non-probability sampling technique. Posed smile photographs were taken using a digital Nikon camera D5300 (105-mm lens) under constant camera settings. Each photograph was imported to Computer software AutoCAD 2017 and calibrated using millimeter markings on the L-shaped metallic scale which was held along the face while taking the photographs. The gingival display was scored as being present or absent. To measure the extent of exposure of the upper central incisor, the length of the tooth visible during the smile was measured from the inferior border of the upper lip to the incisal edge of the maxillary central incisor. Statistical analysis of data was done using Statistical Package for social sciences (SPSS) software version 23. The statistical test applied was the Pearson Chi-square test and independent-sample T-test. The level of significance was kept at 0.05. Results: Out of 154 subjects 43% were males and 57% were females. A statistically non-significant relationship of gender was observed with gingival display (p-value >0.05) and amount of exposure of maxillary central incisor (p-value >0.05) during a smile. Conclusion: Gingival display and amount of maxillary central incisor display are not affected by gender in the studied sample Keywords: Gingival display, gender, maxillary incisor exposure, smile characteristics